Mass production and cost reduction of scientific apparatus for schools in the Philippines - Riola, Robert Aguada 1941- (1970)
Science education in elementary and high schools in the Philippines is being geared toward student participation in classroom experiments. However, local student-oriented scientific apparatus are not readily available and are too highly priced. This study presents means of reducing cost of student-oriented scientific apparatus, of mass producing these apparatus, and of estimating their manufacturing cost.
Thesis (M.S. Industrial Engineering)--University of the Philippines, Diliman.
Keywords: Scientific apparatus and instruments